Carbon components in organic amendments drive nitrogen metabolism in one-year-long anaerobic soil microcosms - Ma, Yiming; Wu, Qiaoyu; Wang, Xinhui; Sui, Weikang; Zhang, Xiaojun (Frontiers in Microbiology, 2025)
IntroductionLong-term studies on the dynamic changes in nitrogen metabolism and functional microbial communities under anaerobic conditions, particularly those driven by organic amendments, remain scarce.MethodsWe conducted a year-long anaerobic microcosm experiment using three organic amendments—aerobically fermented pig-manure digestate (ACM), compost (ACP) and straw powder (ACS)—alongside an inorganic fertilizer-only control (ACN).ResultsTemporal shifts revealed that organic amendments drove distinct nitrogen metabolism pathways. Amendments of digestate and compost promoted the proliferation of nitrogen-mineralizing bacteria such as Ramlibacter and Lysobacter, leading to significant ammonium accumulation. After 12-month incubation, the ACM treatment caused a 75.6-fold increase in ammonium, a 43.4% rise in total nitrogen (TN), and a 27.0% increase in total organic carbon (TOC). In contrast, the ACS treatment exhibited superior nitrogen fixation, with an average of 1.69-fold higher rate than ACM and 5.30 fold higher than ACP The ACS treatment enriched cellulolytic nitrogen-fixing bacteria, including Clostridium, and nitrogen-fixing archaea.DiscussionThis study provides profound insights in to the unique nitrogen metabolism pathways influenced by organic amendments under anoxic conditions, ultimately offering valuable insights into improved soil fertility and sustainable nitrogen management practices in agricultural systems.